Levels of serum vitamin A, alpha-tocopherol and malondialdehyde in patients with non-alcoholic steatohepatitis: relationship with histopathologic severity - Bahcecioglu, IH; Yalniz, M; Ilhan, N; Ataseven, H; Ozercan, IH (Wiley, 2005)
The aims of our study were to estimate serum levels of malondialdehyde (MDA), serum levels of vitamin A and alpha -tocopherol as antioxidants and determine relationship of these with histopathologic severity in patients with non-alcoholic steatohepatitis (NASH). Twenty-nine patients with biopsy-proven NASH were included to study. NASH were histopathologically scored for grading and staging. Serum MDA and vitamin A levels were increased in patients with NASH and simple steatosis as compared to healthy control group. Serum alpha-tocopherol levels measured in simple steatosis and NASH were significantly lower than in healthy control group There was no significant difference between grade/stage 0-1 and grade/stage 2-3 in terms of MDA, vitamin A and alpha-tocopherol levels. Serum MDA and vitamin A levels are increased in simple steatosis and NASH. MDA, vitamin A and alpha-tocopherol levels in NASH were not associated with the histopathologic severity.
Keywords: non-alcoholic steatohepatitis; histopathology; malondialdehyde; alpha-tocopherol; vitamin A